MICROBIOLOGYCAL CHARACTERIZATION AND POTENTIAL APPLICATION OF INDIGENOUS B.METHYLOTROPHYCUS Ba1 IN HANDLING OF CANNA EDULIS. KER PROCESSING CRAFT VILLAGE WASTEWATER - Nhu Ngoc, Nguyen; Van Cach, Nguyen; Lien Ha, Tran; Thi Thuy Giang, Pham (Journal of Forestry Science and Technology, 2016)
Canna edulis. Ker starch processing wastewater from craft villages contains high organic concentration such as starch, cellulose, xylan, protein… and especially high starch concentration after the states of grinding, sedimentation and filtration. The concentration of COD and BOD5, SS and coliform of wastewater are hundreds times higher than standards. To handle and recover organic pollutants of this wastewater, we focus on strains that are able to efficiently convert organic pollutants into biomass. The microbial biomass along with activated sludge – a kind of material can be applied to many other purposes are removed out by settling well while processing. From starch processing sludge and wastewater, strain of Bacillus methylotrophycus Ba1 was selected with notable features: having the ability to use a variety of substrates (starch, cellulose, xylan, protein) with highest amylase activity (D/d = 12.5), COD removed efficiency (90% after 12 hours) and good sedimentation of activated sludge with SVI = 120.4. The results also showed that the optimal conditions for its biomass production: temperature 30oC, initial pH 6.0 and inoculum of 7% (v/v). After 24 hours incubation at these conditions, the highest biomass was measured OD600 of 2.91.